Penapisan Fitokimia, Penetapan Kadar Naftokuinon Total, Dan Aktivitas Antifungi Fraksi Tidak Larut Etil Asetat Ekstrak Etanol Daun Pacar Kuku (Lawsonia inermis L.) Terhadap Candida albicans ATCC 10231 - zainab, zainab; Muthoharoh, Ainun (Pharmaciana, 2015)
Candidiasisis aninfection caused by Candida albicans. Synthetic treatment against Candida albicans have been developed, but reports of resistance to antifungal agents that there continue to emerge, and cause a lot of side effects. Pacar kuku (Lawsonia inermis L.) is one of the plants that have antifungal activity. Chemical contentof polyphenols inhibit candidiasis is a form of naphthoquinone. This study aimed to test the antifungal activity of insoluble ethyl acetate fraction of ethanolic extract of pacar kuku leaves against Candida albicans. Insoluble fraction obtained from the ethyl acetate extraction of previously fractionated with ethyl acetate. Identification of chemical compounds made with phytochemical screening. Test antifungal activity against Candida albicans using microdilution method. Drugs used for comparison is amphoterisin B infusion in doses 250 µg/ml with the concentration of 1,5 µg/ml, 0,75 µg/ml, 0,375 µg/ml, 0,187 µg/ml, 0,0937 µg/ml, dan 0,0469 µg/ml,. The parameters in this study are the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC). The concentration of the fraction used in the MIC and MFC test is the concentration of 80%, 40%, 20%, 10%, 5%, 2,5% w/v. Identification of chemical compounds made with test tubes and assay on anthraquinone compounds. The results showed that the MFC of ethyl acetate insoluble fraction of ethanol extract of leaves pacar kuku is 40% w/v. MIC and MFC amphoterisin B respectively 0,0937 µg/ml and 0,187 µg/ml. Test tubes showed that the ethyl acetate insoluble fraction of ethanol extract of leaves pacar kuku containing polyphenols, saponins, and quinone. The naphtoquinone total content in insoluble ethyl acetate fraction of ethanolic extract of pacar kuku leaves consecutively 7,97±0,14%. The conclusion showed that insoluble ethyl acetate fraction of ethanolic extract of pacar kuku leaves have antifungal activity. Keywords: Lawsonia inermis L., Candida albicans, microdilution, MIC, MFC, naphtoquinone content